Gastrointestinal Dysfunction in Neurological and Neurodegenerative Disorders - Raber, Jacob; Sharpton, Thomas J. (Seminars in Neurology, 2023)
Increasing research links the gut microbiome to neurodegenerative disorders. The gut microbiome communicates with the central nervous system via the gut–brain axis and affects behavioral and cognitive phenotypes. Dysbiosis (a dysfunctional microbiome) drives increased intestinal permeability and inflammation that can negatively affect the brain via the gut–brain axis. Healthier metabolic and lipid profiles and cognitive phenotypes are observed in individuals with more distinct microbiomes. In this review, we discuss the role of the gut microbiome and gut–brain axis in neurodegenerative diseases such as Parkinson's disease and Alzheimer's disease and related animal models, in cancer and cancer treatments, and in metabolic syndrome. We also discuss strategies to improve the gut microbiome and ultimately brain function. Because healthier cognitive phenotypes are observed in individuals with more distinct microbiomes, increased efforts are warranted to develop therapeutic strategies for those at increased risk of developing neurological disorders and patients diagnosed with those disorders.
Keywords: gut microbiome; Parkinson's disease; Alzheimer's disease; radiation; Western diet